PENGARUH RESPONSIVE TERHADAP TINGKAT KEPUASAN MASYARAKAT DI KANTOR DESA BULO KABUPATEN SIDENRENG RAPPANG - Nurul Zalfa Lilah; Jamaluddin; Monalisa Ibrahim (Jurnal Publikasi Manajemen Informatika, 2025)
The purpose of this study was to determine the influence of responsive service on the level of public satisfaction at the Bulo Village Office, Sidenreng Rappang Regency. This study uses a quantitative approach with a descriptive research type. Data collection techniques are carried out through observation, questionnaires, and literature studies. The population in this study was the entire community of Bulo Village, totaling 2,754 people. The sampling technique used the Slovin formula so that 97 respondents were obtained. The data analysis technique used descriptive statistics and multiple linear regression with the help of the SPSS application. The results showed that the responsiveness of service at the Bulo Village Office was classified as good with an average percentage of 65.5%. Meanwhile, the level of public satisfaction was also in the good category with an average percentage of 62.3%. The results of the regression test show that the t-count value > t-table (10.370 > 1.984) means that there is a significant influence between responsive service and the level of public satisfaction. The R square value of 0.525 indicates that the contribution of the influence of responsive service to public satisfaction is 52.6%.